SnO2/Pt thin film laser ablated gas sensor array - Abadi, Mohammad Hadi Nezhad Shahrokh; Hamidon, Mohd Nizar; Shaari, Abdul Halim; Abdullah, Norhafizah; Wagiran, Rahman (MDPI, 2011)
A gas sensor array was developed in a 10 × 10 mm2 space using Screen Printing and Pulse Laser Ablation Deposition (PLAD) techniques. Heater, electrode, and an insulator interlayer were printed using the screen printing method on an alumina substrate, while tin oxide and platinum films, as sensing and catalyst layers, were deposited on the electrode at room temperature using the PLAD method, respectively. To ablate SnO2 and Pt targets, depositions were achieved by using a 1,064 nm Nd-YAG laser, with a power of 0.7 J/s, at different deposition times of 2, 5 and 10 min, in an atmosphere containing 0.04 mbar (4 kPa) of O2. A range of spectroscopic diffraction and real space imaging techniques, SEM, EDX, XRD, and AFM were used in order to characterize the surface morphology, structure, and composition of the films. Measurement on the array shows sensitivity to some solvent and wood smoke can be achieved with short response and recovery times.